A new compound heterozygosis for inactivating mutations in the glucokinase gene as cause of permanent neonatal diabetes mellitus (PNDM) in double-first cousins. Issue 1 (December 2015) - Esquiaveto-Aun, Adriana; Mello, Maricilda; Paulino, Maria; Minicucci, Walter; Guerra-Júnior, Gil; Lemos-Marini, Sofia
Abstract Background Permanent neonatal diabetes mellitus (PNDM) is a rare disorder, characterized by uncontrolled hyperglycemia diagnosed during the first 6 months of life. In general, PNDM has a genetic origin and most frequently it results from heterozygous mutations inKCNJ11, INS andABCC8 genes. Homozygous or compound heterozygous inactivating mutations inGCK gene as cause of PNDM are rare. In contrast, heterozygosis forGCK inactivating mutations is frequent and results in the maturity-onset diabetes of young (MODY), manifested by a mild fasting hyperglycemia usually detected later in life. Therefore, as an autosomal recessive disorder, GCK-PNDM should be considered in families with history of glucose intolerance or MODY in first relatives, especially when consanguinity is suspected. Results Here we describe two patients born from non-consanguineous parents within a family. They presented low birth weight with persistent hyperglycemia during the first month of life. Molecular analyses forKCNJ11, INS, ABCC8 did not show any mutation.GCK gene sequencing, however, revealed that both patients were compound heterozygous for two missense combined in a novel GCK-PNDM genotype. The p.Asn254His and p.Arg447Gly mutations had been inherited from their mothers and fathers, respectively, as their mothers are sisters and their fathers are brothers. Parents had been later diagnosed as having GCK-MODY. Conclusions Mutations' in silico analysis was carried out to elucidate the role of the amino acid changes on the enzyme structure. Both p.Asn254His and p.Arg447Gly mutations appeared to be quite damaging. This is the first report of GCK-PNDM in a Brazilian family.